2015
DOI: 10.1128/iai.00294-15
|View full text |Cite
|
Sign up to set email alerts
|

Selective Requirement of the Shikimate Pathway of Legionella pneumophila for Intravacuolar Growth within Human Macrophages but Not within Acanthamoeba

Abstract: bLegionella pneumophila utilizes the Dot/Icm type IV translocation system to proliferate within a vacuole in a wide variety of natural amoebal hosts and in alveolar macrophages of the human accidental host. Although L. pneumophila utilizes host amino acids as the main sources of carbon and energy, it is not known whether de novo synthesis of amino acids by intravacuolar L. pneumophila contributes to its nutrition. The aroB and aroE genes encode enzymes for the shikimate pathway that generates the aromatic amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…On one hand, in vitro grown L. pneumophila does not need to use this pathway for the de novo biosynthesis of aromatic amino acids and rather imports these amino acids from the medium. On the other hand, recent studies demonstrated that mutants of L. pneumophila concerning two enzymes of the shikimate pathway, aroB and aroE , were defective in infection and replication inside of human macrophages (Jones et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, in vitro grown L. pneumophila does not need to use this pathway for the de novo biosynthesis of aromatic amino acids and rather imports these amino acids from the medium. On the other hand, recent studies demonstrated that mutants of L. pneumophila concerning two enzymes of the shikimate pathway, aroB and aroE , were defective in infection and replication inside of human macrophages (Jones et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon from glucose was detected in amino acids and in PHB, and only a minor enrichment was found in mannose . The importance of available amino acids for the replication of L. pneumophila within the LCV was also shown in further experiments using different mutant strains . The data indicate that different substrates can be metabolized independently during the replicative phase .…”
Section: Host‐adapted Metabolism Of L Pneumophilamentioning
confidence: 73%
“…In addition, PhtJ was identified as a Val transporter also essential for differentiation and intracellular multiplication of L. pneumophila in macrophages . Recently, it was demonstrated that aroA and aroB , involved in the biosynthesis of aromatic amino acids, are also essential during intracellular replication of L. pneumophila in macrophages . Furthermore, transcriptomic studies demonstrated the upregulation of genes encoding transporters for amino acids and oligopeptides as well as enzymes involved in the metabolism of Glu, Gln, Thr, Lys, Arg and His during intracellular replication .…”
Section: Host‐adapted Metabolism Of L Pneumophilamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, LamA augments IFN-γ-mediated IDO1 activity, which depletes cellular tryptophan. Although L. pneumophila is not auxotrophic for tryptophan, host-derived tryptophan is important for L. pneumophila replication within macrophages [ 192 , 193 ].…”
Section: Effector-mediated Nutrient Acquisition and Modulation Of Hosmentioning
confidence: 99%